Towards Adapting BitTorrent for Interactive On-Demand Multimedia Streaming over MANETs - Rodrigues, Carlo K. da Silva; Rocha, Vladimir E. M. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
This paper proposes two novel adaptations of the BitTorrent algorithm for interactive on-demand multimedia streaming over mobile ad hoc networks (MANETs). The first adaptation follows the layered-architecture paradigm, while the second explores the crosslayer alternative. The design of both proposals mainly lies on combining distinct criteria to more adequately select peers and request data in the presence of communication channels changing on a continual basis. By means of simulations on various scenarios, characterized by client mobility and interactivity, the adaptations are evaluated through different metrics that may jointly capture the system QoS. Among the major findings, the final results highlight the effectiveness of our proposals compared to recent related work. Within this context, the key contribution of this paper is to provide valuable algorithmic insights for real-world protocol designs targeted at MANETs. Lastly, avenues for further research are included at the end of the paper.